Prevalence, Treatment Status, and Comorbidities of Hyperthyroidism in Korea from 2003 to 2018: A Nationwide Population Study - Ahn, Hwa Young; Cho, Sun Wook; Lee, Mi Young; Park, Young Joo; Koo, Bon Seok; Chang, Hang-Seok; Yi, Ka Hee (Endocrinology and metabolism (Seoul), 2023)
Background: This study aimed to investigate the changes of incidence and treatment of choice for hyperthyroidism from 2003 to 2018 and explore the treatment-related complications and concomitant comorbidities in South Korea using data from the National Health Insurance Service.Methods: This is a retrospective observational study. Hyperthyroidism was defined as a case having two or more diagnostic codes of thyrotoxicosis, with antithyroid drug intake for more than 6 months.Results: The average age-standardized incidence of hyperthyroidism from 2003 to 2018 was 42.23 and 105.13 per 100,000 men and women, respectively. In 2003 to 2004, hyperthyroidism was most often diagnosed in patients in their 50s, but in 2017 to 2018, people were most often diagnosed in their 60s. During the entire period, about 93.7% of hyperthyroidism patients were prescribed with antithyroid drugs, and meanwhile, the annual rates of ablation therapy decrease from 7.68% in 2008 to 4.56% in 2018. Antithyroid drug-related adverse events, mainly agranulocytosis and acute hepatitis, as well as complications of hyperthyroidism such as atrial fibrillation or flutter, osteoporosis, and fractures, occurred more often in younger patients.Conclusion: In Korea, hyperthyroidism occurred about 2.5 times more in women than in men, and antithyroid drugs were most preferred as the first-line treatment. Compared to the general population, hyperthyroid patients may have a higher risk of atrial fibrillation or flutter, osteoporosis, and fractures at a younger age.